2011
DOI: 10.2478/v10011-011-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase: New Roles for an Old Molecule

Abstract: Myeloperoxidase (MPO) is a member of the heme peroxidase-cyclooxygenase superfamily. It is abundantly expressed in neutrophils and monocytes. During inflam mation MPO is released from leukocytes and catalyzes the formation of several reactive species and tissue damage. In this article we present state of the art knowledge on the general properties, biosynthesis and processing and trafficking of MPO. The basic functions of MPO in inflammation and oxidative stress are discussed in detail. This article also summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Lactoperoxidase (LPO) and myeloperoxidase (MPO) are two important heme-containing peroxidases involved in the immune defense system [5558]. Both defend the system from invading microorganism by the bactericidal activities of the oxidized substrates [56, 59]. For example, MPO catalyzes the formation of hypochlorous acid (HOCl) from chloride species and H 2 O 2 , which has antimicrobial activity and kills other pathogens in humans [59].…”
Section: Interaction Of H2s With Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactoperoxidase (LPO) and myeloperoxidase (MPO) are two important heme-containing peroxidases involved in the immune defense system [5558]. Both defend the system from invading microorganism by the bactericidal activities of the oxidized substrates [56, 59]. For example, MPO catalyzes the formation of hypochlorous acid (HOCl) from chloride species and H 2 O 2 , which has antimicrobial activity and kills other pathogens in humans [59].…”
Section: Interaction Of H2s With Enzymesmentioning
confidence: 99%
“…Both defend the system from invading microorganism by the bactericidal activities of the oxidized substrates [56, 59]. For example, MPO catalyzes the formation of hypochlorous acid (HOCl) from chloride species and H 2 O 2 , which has antimicrobial activity and kills other pathogens in humans [59]. In the resting form, the heme groups of LPO and MPO are penta-coordinated with the iron in the high spin ferric state.…”
Section: Interaction Of H2s With Enzymesmentioning
confidence: 99%
“…15 The reason for increased MPO concentrations in heparin samples in the study conducted by Shih et al 15 may be due to the fact that heparin helps in stimulating release of MPO from leukocytes and activates neutrophils during blood coagulation. 5 Scheffer et al 16 reported that MPO concentrations remained comparatively constant in heparin samples, when stored on ice, while storage of samples at room temperature for 2 h resulted in four-fold increase in MPO concentrations in heparin samples 16 (means temperature can cause an increase in MPO concentrations in heparin tubes).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in MPO concentrations may occur during the early stages of ACS, even prior to the evidence of myonecrosis, probably reflecting instability of atherosclerotic plaque. 5 Several studies have reported that MPO concentrations may provide prognostic information in ACS patients. [6][7][8] A few important studies have investigated the role of MPO for risk stratification of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been de tected that the amount of GSH is parallel with the expression of the GCLC gene, of which the expression re gulated at the transcriptional level comes first (16)(17)(18). On the other hand, effects of the -3506A/G ve -129C/T polymorphisms which occur independently at the promoter region of the GCLC gene have been investi gated in myo cardial infarction (MI) and it has been observed that -129C/T polymorphism is in creased in individuals who have MI with respect to those who do not (19,20). Thus, GCLC is an essential enzyme for the glutat hio ne mechanism, and further comprehensive studies are needed in order to understand the effects of alte rations in this gene.…”
Section: Introductionmentioning
confidence: 99%